Future champions: 270 names to watch closely - Poli, Raffaele; Besson, Roger; Ravenel, Loïc (My University, 2023)
This report highlights the players born in 2003 or later who have accumulated the most playing experience over the last year (as at 11 December 2023), according the exclusive CIES Football Observatory ‘experience score’ metrics, in nine positions: goalkeepers, centre backs, left backs, right backs, holding midfielders, attacking midfielders, left wingers, right wingers and centre forwards.
Keywords: football; talent; performance; scouting